RESONATING STRUGGLES: IDENTIFYING POST-SURGERY SPEECH DISORDERS AMONG CLEFT LIP SUFFERERS AT YAYASAN UMMI ROMLAH - Nastiti, Dian; Muhammad Iqbal Ramdhani (JTH: Journal of Technology and Health, 2024)
This research investigates the speech disorders experienced by individuals who have undergone cleft lip surgery at Yayasan Ummi Romlah. The study aims to identify the specific types of speech disorders resulting from cleft lip sufferer after the surgery, as well as to determine which sounds remain difficult to articulate after the procedure. The research contributes to a deeper understanding of the speech challenges faced by cleft lip and palate patients following surgery. Employing a qualitative method, the study encompasses data collection and analysis techniques. Language utterances from cleft lip patients, primarily obtained through dialogues using the "Simak, Rekam, Catat" method, constitute the study's data. Through listening and recording language usage, the research captures important points from interviews and reading text. The research entails interviewing patients to gain insights into their experiences and identifying the specific phonemes, words, and sentences that pose pronunciation challenges. Video recordings of patients' speech are also collected for subsequent analysis. It reveals that certain patients struggle with enunciating vowels such as /a/ and /i/. Furthermore, difficulties arise in pronouncing consonant sounds, including /r/, /g/, /h/, /k/, and /n/. These challenges are attributed to imperfections in the speech apparatus stemming from the lip, palate, throat, and nose. Remarkably, despite surgical interventions, common speech disorders among the patients involve voice and articulation irregularities, resulting in nasally and roughly produced sounds. The findings illuminate the enduring impact of cleft lip on speech coordination and suggest that surgical enhancements may not entirely mitigate speech difficulties.